Hysterosalpingography Findings among Women Presenting for Infertility Evaluation - Madeeha Riaz, Sadia Faiz, Rubia Fatima, Khadija Sattar, Zia Ul Islam, Atqa Firdous, MM Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the pattern of hysterosalpingography (HSG) findings among women presenting with infertility. Methods: From June 2021 to March 2022, this study included 100 women who visited the Nishtar hospital's infertility clinic. All these patients underwent HSG evaluation. The HSG examination was planned to take place between the seventh and twelfth day of the patient's menstrual cycle, and before the patient had any sexual activity. Patients were instructed to take a nonsteroidal anti-inflammatory medication such 400 milligrams of ibuprofen half an hour before their hysterosalpingograms as a preparation for the possibility that they may experience some level of discomfort during the procedure. HSG findings were noted for each patient. Results: The mean of participants was 32.5±1.2 years. Mean infertility duration was 5.5±4.3 years. On hysterosalpingography examination, right fallopian tube occlusion was found in 7% patients, left in 13% and bilateral in 25% patients. Hydrosalpinx was diagnosed in right fallopian tube in 7.0% patients, in left in 5% patients and in both fallopian tubes in 3% patients. Overhanging tubes were diagnosed in 8% patients and beaded tubes in 1.0% patients. Regarding uterine pathologies, fibroids were diagnosed in 21% patients, and synaechiae in 8% patients. Regarding cervical pathologies, irregular pattern was found in 2% patients, patulous in 2% and in stenosis in 1.0% patients. Conclusion: Hysterosalpingogram, an essential instrument in the evaluation of infertility, plays a significant part in identifying illnesses that affect the female reproductive system. According to the findings of this study, tubal diseases are the leading cause of female infertility. Keywords: Infertility, Tubal abnormalities, Hysterosalpingogram